Quorum Sensing System-Regulated Proteins Affect the Spoilage Potential of Co-cultured Acinetobacter johnsonii and Pseudomonas fluorescens From Spoiled Bigeye Tuna (Thunnus obesus) as Determined by Proteomic Analysis - Wang, Xin-Yun; Xie, Jing (Frontiers in Microbiology, 2020)
Food spoilage by certain species of bacteria is reported to be regulated by quorum sensing (QS). Acinetobacter johnsonii and Pseudomonas fluorescens, the major specific spoilage organisms, are found to be limited in their QS and co-culture interactions. The aim of this study was to determine how QS-regulated proteins affect the spoilage potential of co-cultured A. johnsonii and P. fluorescens obtained from spoiled bigeye tuna (Thunnus obesus) using a proteomics approach. The A. johnsonii, P. fluorescens, and their co-culture tested the N-acyl-homoserine lactone (AHL) activities using reporter Chromobacterium violaceum CV026 and LC-MS/MS in qualitative and quantitative approaches, respectively. These showed that, of the 470 proteins and 444 proteins in A. johnsonii (A) and P. fluorescens (P), respectively, 80 were significantly up-regulated and 97 were significantly down-regulated in A vs. AP, whereas 90 were up-regulated and 65 were down-regulated in P vs. AP. The differentially expressed proteins included the AI-2E family transporter OS, 50S ribosomal protein L3, thioredoxin reductase OS, cysteine synthase CysM OS, DNA-binding response regulator, and amino acid ABC transporter ATPase OS. The cellular process (GO:0009987), metabolic process (GO:0008152), and single-organism process (GO:0044699) were classified into the gene ontology (GO) term. In addition, energy production and conversion, amino acid transport and metabolism, translation, ribosomal structure and biogenesis, post-translational modification, protein turnover, and chaperones were distributed into the clusters of orthologous groups of proteins (COG) terms. The KEGG pathways revealed that 84 and 77 differentially expressed proteins were divided into 20 KEGG pathways in A vs. AP and P vs AP, respectively, and amino acid metabolism, carbohydrate metabolism, energy metabolism, and translation were significantly enriched. Proteins that correlated with the spoilage-related metabolic pathways, including thioredoxin reductase OS, cysteine synthase OS, and pyridoxal phosphate-dependent enzyme family protein OS, were identified. AI-2E family transporter OS and LuxR family transcriptional regulator OS were identified that related to the QS system. These findings provide a differential proteomic profile of co-culture in A. johnsonii and P. fluorescens, and have potential applications in QS and the regulation of spoilage potential.